Gentle Birth Delivery Method With Level Of Labor Pain at PMB Griya Bunda Sehat Balikpapan - Endah Wijayanti; Grace Carol Sipatulta; Ita Kusumayanti; Vima Eka Astika; Ernani Setyawati; Damai Noviasari; Eli Rahmawati; Sekar handayani (Window of Health : Jurnal Kesehatan, 2026)
Gentle birth is a birthing approach characterized by a calm, gentle, respectful, and courteous process that optimally utilizes the natural integration between body, mind, and spirit. Globally, the prevalence of gentle birth practices has increased in line with the growing demand for humanistic and minimally medical interventions in childbirth. Studies report that 20–40% of pregnancy care facilities in developed countries have adopted elements of gentle birth, such as relaxation techniques, emotional support, controlled breathing, minimal medical intervention, and a supportive birthing environment. In a gentle birth, the mother is directed to perceive pain as something that will help her to meet the baby. The aim of his study is to find out the relationship between the gentle birth delivery method and the level of labor pain in women giving birth at PMB Griya Sehat Balikpapan in 2024. Quantitative research with an analytical observational research type. The sampling method in this research was non-probability sampling using an accidental sampling technique with a sample size of 45 people plus 10% to account for sample dropout. This research uses cross-sectional study analysis techniques. The statistical test results of this study indicate a significant relationship between gentle birth methods (independent variable) and the level of labor pain (dependent variable) in women who gave birth at PMB Griya Sehat Balikpapan in 2024 (p < 0.05). These findings indicate that the application of gentle birth methods is associated with a decrease in pain levels during childbirth. It can be concluded that mothers who used the gentle delivery method during labor at PMB Griya Bunda experienced mild labor pain. Based on these findings, the gentle delivery method can be recommended as an alternative non-pharmacological strategy for managing labor pain in obstetric services.